Revision of genera Gaza and Callogaza (Vetigastropoda, Trochidae), with description of a new Brazilian species - Simone, Luiz Ricardo L.; Cunha, Carlo M. (Zootaxa, 2006)
A revision of the trochid genera Gaza and Callogaza, inhabiting the deep waters of western Atlantic Ocean and eastern Pacific Ocean, is here provided. Species are separated mainly by shell characters, but anatomical features are also used in some species. The species considered in this study are: Gaza compta n. sp. (SE Brazil), G. daedala Watson, 1879 (Central Pacific), G. rathbuni Dall, 1890 (tropical W Pacific), G. fischeri Dall, 1889 (E Caribbean), G. superba (Dall, 1881) (Gulf of Mexico and Caribbean), G. cubana Clench & Aguayo, 1940 (N Caribbean), G. olivacea Quinn, 1991 (NE South America and SE Brazil), Callogaza watsoni Dall, 1881 (Gulf of Mexico), C. sericata (Kira, 1959) (NW Pacific) and C. frederici (Smith, 1906) (S India). Anatomical data are provided for: Gaza compta, G. olivacea, G, fischeri, G. superba and G. cubana. Both Gaza and Callogaza are characterized by having iridescent, thin-walled shell, with the outer lip deflected (determined growth), and a flat callus partially or completely covering the wide umbilicus, making it a hollow chamber. Anatomically, the examined Gaza spp. have long epipodial tentacles and two series of holes between the propodium and the base of the head. The number of these structures can assist in the differentiation of species. Based on similarities of the shell and comparison with species of other trochid genera, we conclude that Gaza and Callogaza have some characters in common, which most probably constitute synapomorphies that support a monophyletic branch of the family. Microgaza is not regarded as part of this trochid branch, but may rather belong to Solariellinae.